Acquired childhood bladder melanosis - Roma Subhash Varik; Mudher Al-Adhani; Arash Taghizadeh (SpringerOpen, 2022)
Abstract Background Bladder melanosis is rare. It has previously been described only in the fifth decade of life or beyond; it has not been described in childhood. Previous descriptions have generally been case reports, and so the natural history is poorly understood. Urinary symptoms present at the time of cystoscopy have frequently been attributed to bladder melanosis. A possible suggested aetiology is aberrant migration of melanocyte migration during embryogenesis. Case presentation We present the first case of bladder melanosis in a child. He had been under our care since the age of 5 years with urinary incontinence and at that time, had undergone cystoscopy demonstrating normal bladder mucosa. A diagnosis of idiopathic detrusor overactivity with underactive voiding had been made. After other unsuccessful treatments, intravesical botulinum toxin was proposed. At the age of 13, repeat cystoscopy prior to botulinum toxin, demonstrated widespread pigmented areas in the bladder mucosa. Histology showed bladder melanosis. Our finding is important for several reasons. This is the first reported case of bladder melanosis to affect a child. The previous normal cystoscopy in our patient would refute the explanation that bladder melanosis is a congenital condition. Furthermore, the development of melanosis on the background of stable symptoms raises the possibility that the condition may be asymptomatic. Conclusions This unique finding of bladder melanosis in a child has provided further insight into this rare and poorly understood condition.